2013
DOI: 10.1088/0031-9155/58/21/7841
|View full text |Cite
|
Sign up to set email alerts
|

An x-ray fluorescence imaging system for gold nanoparticle detection

Abstract: Gold nanoparticles (GNPs) may be used as a contrast agent to identifytumour location and can be modified to target-and image-specific tumour biological parameters. There are currently no imaging systems in the literature that have sufficient sensitivity to GNP concentration and distribution measurement at sufficient tissue depth for use in in vivo and in vitro studies. We have demonstrated that high detecting sensitivity of GNPs can be achieved using x-ray fluorescence; furthermore this technique enables highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Recently published work highlights the development of a new GNP imaging method that works by detecting the L-edge x-ray fluorescence emitted when gold is irradiated with kV energy x-rays. The technique is said to achieve increased detection sensitivity at greater depths than current optical modalities [165]. More of such developments would be a very useful advance for developing GNRT.…”
Section: Future Perspectivementioning
confidence: 99%
“…Recently published work highlights the development of a new GNP imaging method that works by detecting the L-edge x-ray fluorescence emitted when gold is irradiated with kV energy x-rays. The technique is said to achieve increased detection sensitivity at greater depths than current optical modalities [165]. More of such developments would be a very useful advance for developing GNRT.…”
Section: Future Perspectivementioning
confidence: 99%
“…This method could be of great interest once there are imaging systems in place that have sufficient sensitivity to NP concentrations and, at the same time, are capable of distribution measurements at appropriate tissue depths for in vivo and in vitro studies [100,101]. Consequently, Ricketts et al reported that a high detecting sensitivity of AuNPs can be achieved using x-ray fluorescence, enabling a greater depth imaging in comparison with optical modalities [101].…”
Section: Bioimaging Using Aunpsmentioning
confidence: 99%
“…Compared to its counterpart based on gold K-shell XRF photons (~67 and~68.8 keV), [4][5][6][7] this approach referred to as benchtop L-shell XRF imaging or XFCT has been shown to provide a much lower GNP (or gold) detection limit, typically on the order of parts-permillion (ppm). 1,2 This drastic improvement in the detection limit (e.g., by two orders of magnitude) can be attributed to much lower scatter background as well as the availability of x-ray detector with much higher detection efficiency/energy resolution around gold L-shell XRF peaks, all of which immensely facilitate the extraction of gold L-shell XRF peaks from the Compton scatter background.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,8,9 In previous imaging studies with L-shell XRF photons, attenuation correction was achieved through either transmission CT images 8 or the calculation of the ratio of XRF-to-Compton scatter counts. 1,2 Compared to a relatively straightforward CT image-based approach (for XFCT), the latter approach (for direct XRF imaging) is based on the fact that the Compton scatter has little dependence on the material density at this energy range; thus, measured Compton scattered photon counts can be used to correct for the attenuation of the excitation beam. 10,11 This approach, however, was proposed mainly to correct for selfabsorption in small samples encountered in XRF analysis.…”
Section: Introductionmentioning
confidence: 99%